The Relationship of Knowledge and Attitude With Giving Vitamin A Capsules to Postpartum Mothers In The Tanjung Marulak Health Center Work Area - Helti, Mestika Riza; Wahyuni, Faradita (International Archives of Medical Sciences and Public Health, 2024)
Background; Menstruation is an important event in the life of a young woman. Some adolescents experience disturbances during menstruation, namely experiencing pain during menstruation (dysmenorrhea). Menstrual pain management is divided into two categories, namely pharmacological and non-pharmacological approaches. One of the non-pharmacological treatments is giving carrot juice. This study aims to determine the effect of giving carrot juice (daucus carota) to reducing dysmenorrhea pain in female students at SMP Negeri 10 Tebing Tinggi City in 2022. Method; This type of research is a quasi experiment using a one-group pretest-posttest design. The population of this study were all 93 class IX students at SMP Negeri 10 Tebing Tinggi City. The sampling technique used the Lemeshow formula as many as 15 people. Then the method of sampling is done by purposive sampling. The type of data used is primary and secondary data collected using observation sheets then processed and analyzed using paired t-test. Results; The results showed that the majority of dysmenorrhea pain in the pretest group was moderate pain as many as 11 people (73.3%). After being given carrot juice, there was a decrease in dysmenorrheal pain to mild pain in 12 people (80.0%). Statistical test results obtained p-value = 0.000. Conclusion; The conclusion is that there is an effect of giving carrot juice (daucus carota) to reduce dysmenorrhoea pain. For this reason, for young women to be able to use carrots to make juice to reduce menstrual pain as a non-pharmacological method that is safe and easy to obtain at home.